The Impact Between Non-audit Services and Auditor Independence in UK - KE, YAN (2012)
This research examines whether the provision of non-audit services from the incumbent auditor would impact auditor independence based on Ashbaugh et al.(2003)’s empirical tests. Using data collected from financial statements of listed UK firms, the results of tests are contrast to Ashbaugh et al. (2003)’s results which are based on US sample firms. It shows that non-audit fees are negative significant associated with signed discretionary accruals in the UK environment, which indicates that the purchasing of non-audit services from their incumbent auditors are more likely to improve auditor independence. In additional sensitive analysis, Frankel et al. (2002)’s empirical tests are used to investigate robustness of prior research. Similar results are found from these tests. Yet, for the above tests, no relation between ratio of non-audit fees to total fees and discretionary accruals has been found. Moreover, depend on auditor size, the effect of non-audit services on auditor independence wouldn’t impact discretionary accruals for firms with big 4 auditor. However, using the ‘unexpected’ non-audit fees, no significant association has been reported for any types of discretionary accruals in this study. These results provide some evidences for concerns about the effect of non-audit services on auditor independence and audit quality.